Status of Soil Fertility in a Community Forest of Nepal - KC, Anup; Bhandari, Govinda; Wagle, Subigya Prabhat; Banjade, Yubraj (International Journal of Environment, 2013)
Soil is a complex mixture of mineral nutrients, organic matter, water, air and living organisms. The primary nutrients for plant growth are organic matter, nitrogen, phosphorus and potassium. In order to find the status of pH, organic matter (C), total nitrogen (N), available phosphorus (P) and available potassium (K) in forest soil, the study was conducted in Ghwangkhola Sapaude Babiyabhir Community Forest in Putali Bazaar Municipality-8, Syangja, Nepal. Soil parameters are analyzed through different standard methods followed worldwide by many soil scientists. Soil pH of sample in all three strata was slightly acidic and varies from 5.7 to 7.18. The carbon percentage was high and varies from 0.65% to 2.39%. The total nitrogen in soil was medium and varies from 0.09% to 0.12%. The concentration of available phosphorus in soil was high and varies from 73.71 kg/ha-93.23 kg/ha. The concentration of available potassium on soil was quiet low and varies from 2.54 kg/ha-4.23 kg/ha. Higher organic matter in the forest land indicate low activities of nitrogen losing process, which is due to the closed nutrient cycling and minimal disturbance in the natural forest system. So, addition of fertilizer rich in potassium and increasing pH is recommended to maintain potassium fertility and neutral pH in the forest soil. DOI: http://dx.doi.org/10.3126/ije.v1i1.8528 International Journal of Environment Vol.1(1) 2013: 56-67